STORY MAP IN IMPROVING STUDENTS' READING COMPREHENSION OF NARRATIVE TEXT - Hanifa, Iftikari Fauzia (2016)
This study focuses on investigation of how story map is implemented in teaching narrative text in a junior high school in Bandung and how the teaching of story map improves students' reading comprehension in learning narrative text. To achieve the purposes, this study employed qualitative approach which settled case study design. This study involves eighth grade students as the research participants. The data are collected from classroom observation, interview, and reading comprehension test. This study reveals several steps in implementing the story map while learning narrative text: (1) the introduction to story map; (2) filling each element of story map; and (3) discussion and reviewing. Besides, the writer also finds several ways a story map improves students' reading comprehension in learning narrative text, that are (1) story map builds upon prior knowledge, and (2) story map helps to organize story content. Story map gives good impacts for students, most of the students give positive responses. It is supported by the fact that they enjoyed their reading comprehension process using story map. Based on the findings, teacher needs to be more creative in selecting teaching learning technique in improving students' reading comprehension. In addition, it can enrich study about reading comprehension techniques in Indonesia.